Nanotechnology in cancer and insulin therapy - Aminabhavi, Tejraj (Henry Stewart Talks, 2021)
Nanotechnology, Cancer therapy, Insulin therapy, Nanoparticles, Polymer chemistry, Drug design, Coated vs. uncoated drugs, Controlled drug delivery